Advances in animal conservation genetics (Zoological Records and Reviews, 2025)
Conservation genetics -- the application of genetic and genomic tools to the conservation and management ofbiodiversity -- has undergone a profound transformation over the past decade, driven by the dramatic cost reduction ofwhole-genome sequencing, the development of population genomics analytical frameworks, and the maturation ofnon-invasive genetic sampling methods that enable population-level genomic data collection without physical capture.This review synthesises advances in animal conservation genetics from 208 primary studies (2010-2025), evaluatingdevelopments across six application domains: population structure and connectivity analysis, inbreeding and geneticdiversity assessment, adaptive genetic variation and climate change vulnerability, genetic species identification andtaxonomy, kinship and pedigree reconstruction, and environmental DNA for occupancy and abundance estimation.Whole-genome sequencing has revealed previously undetected population structure in 84% of re-assessed Europeanvertebrate species, with direct implications for management unit delineation and translocation suitability. Runs ofhomozygosity (ROH) analysis from low-coverage whole-genome data now provides individual-level inbreedingcoefficients with accuracy exceeding pedigree-based estimates for wild populations. Landscape genomics approacheshave identified climate-adaptive allele variants in 42 European vertebrate species, enabling proactive translocation ofpre-adapted genotypes ahead of projected climate velocity. Close-kin mark-recapture from non-invasive genetic samplesprovides abundance estimates comparable in accuracy to intensive camera trap surveys for large carnivores. A decisionframework for genomic tool selection in European conservation management contexts is presented, with guidelines forminimum sample sizes, sequencing strategies, and analytical workflows aligned with EU Habitats Directive Article 17reporting requirements.